Influence of amino acid variations in the NS3, NS4A and NS4B of HCV genotypes 1a, 1b, 3a, 3b and 6f on the response to pegylated interferon and ribavirin combination therapy - Chusri,P. (Elsevier, 2015)
© 2014 Elsevier B.V. Background: It has been suggested that HCV proteins, core, NS3/4A, NS4B, and NS5A, contribute to the resistance of HCV to IFN and ribavirin (RBV) treatments. Aim: To assess the effects of HCV amino acid variations in NS3, NS4A and NS4B of HCV subtypes 1a, 1b, 3a, 3b and 6f on the response to pegylated interferon (Peg-IFN) and RBV therapy. Methods: One hundred and thirty four HCV isolates of genotypes 1a, 1b, 3a, 3b and 6f obtained from HCV patients both before and at week 4 of treatments were evaluated. Amino acid sequences of NS3, NS4A and NS4B were analyzed and in compared to reference sequences of corresponding genotypes. Results: The data revealed that amino acid variations within the full-length NS3, protease and helicase domains of NS3 of HCV 1a from responders were significantly higher than those from treatment failure groups as compared to reference sequences of each corresponding genotype. Similar results were observed in the full-length and helicase domain but not in the protease domain of HCV 1b. However, the number of amino acid variations in NS3 of HCV 3a, 3b and 6f as well as in NS4A and NS4B showed no difference between the viruses from responders and treatment failure group. Analysis of amino acid variations both before and at week 4 of treatment revealed that the mean number of amino acid variation in the full-length NS3 of HCV 3a and 3b from responders were also significantly higher than those from the treatment failure group. Conclusion: Our study suggests that the increase of amino acid variations within the NS3 protein of HCV 1a, 1b, 3a and 3b were associated with the response to Peg-IFN and RBV treatment in Thai patients.